PERBANDINGAN KONSEP RIBA DAN BUNGA BANK MENURUT YUSUF QARADHAWI DAN MUHAMMAD SAYYID THANTAWI SERTA IMPLIKASINYA TERHADAP PERBANKAN SYARIAH - Annisa Eka Rahayu; Neneng Nurhasanah; Nandang Ihwanudin (ITB AAS INDONESIA Surakarta, 2021)
Banks exist to be the power of human economy. Problems arise related to the banking system which has narrowed to interest, it has become a controversial topic of discussion. This led to differences of opinion among contemporary scholars such as Yusuf Qaradhâwi and Muhammad Sayyid Thantawi. This difference in opinion regarding the status of interest can affect public interest in conducting transactions with banks. The purpose of this study is to analyze the legal status of bank interest according to Yusuf Qaradhâwi and Muhammad Sayyid Thantawi and to find out its impact on the market share of Islamic banking in Indonesia. The research method used is a qualitative method with literature study. Based on the research results, the law of interest according to Muhammad Syyid Thantawi is not a prohibited riba. The istinbâth ahkam method used by Thantawi in determining the status of bank interest is Al-Qur'an, hadith, qiyas, and mashlahah mursalah. According to Yusuf Qaradhâwi, the law of interest is the same as usury. The istinbâth ahkam method used by Yusuf Qaradhâwi in determining the status of interest is Al-Qur'an, hadith, Ijma 'ulama, qiyas, and fiqh rules. Thantawi's thinking has implications for the paradigm of public thinking that the Islamic financial industry still tends to be conventional. Qradhawi's Opinion This needs to be supported considering the large number of Muslims in Indonesia, this is expected to change the paradigm of thinking of the public to conduct transactions with Islamic banks, as to increase the market share of Islamic banking in Indonesia. Keywords : Riba, Interst, Yusuf Yusuf Qaradhâwi, Muhammad Sayyid Thantawi and Market Share.